Experimental evidence of intrabeam scattering in a free-electron laser driver. (19th August 2020) - Di Mitri, S; Perosa, G; Brynes, A; Setija, I; Spampinati, S; Williams, P H; Wolski, A; Allaria, E; Brussaard, S; Giannessi, L; Penco, G; Rebernik, P R; et al.
Abstract: The effect of multiple small-angle Coulomb scattering, or intrabeam scattering (IBS) is routinely observed in electron storage rings over the typical damping time scale of milliseconds. So far, IBS has not been observed in single pass electron accelerators because charge density orders of magnitude higher than in storage rings would be needed. We show that such density is now available at high brightness electron linacs for free-electron lasers (FELs). We report measurements of the beam energy spread in the FERMI linac in the presence of the microbunching instability, which are consistent with a revisited IBS model for single pass systems. We also show that neglecting the hereby demonstrated effect of IBS in the parameter range typical of seeded VUV and soft x-ray FELs, results in too conservative a facility design, or failure to realise the accessible potential performance. As an example, an optimization of the FERMI parameters driven by an experimentally benchmarked model, opens the door to the extension of stable single spectral line emission to the water window (2.3–4.4 nm), with far-reaching implications for experiments in a variety of disciplines, ranging from physics and chemistry to biology and material sciences, and including nonlinear x-ray optics based on the four-wave-mixing approach.